PENGARUH PROFITABILITAS DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK : THE EFFECT OF PROFITABILITY AND TRANSFER PRICING ON TAX AVOIDANCE - Ernawati, Diana; Simbolon, Remista (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The biggest revenue for a country comes from taxes, which will be an obligation for every taxpayer to fulfill. The taxpayer in question is a corporation. This research was conducted in order to know what kind of influence on tax avoidance is caused by profitability and transfer pricing. The research was conducted in the cement, ceramics, porcelain, and glass subsectors on the Indonesia Stock Exchange list from 2017 to 2022 and applied a technique, namely purposive sampling, so that 36 samples were obtained. Profitability and transfer pricing are used as independent variables, and tax avoidance is used as an a dependent variable. The results found that profitability has a significant negative effect on tax avoidance. Similarly, transfer pricing also has an influence on tax avoidance. As for profitability and transfer pricing on tax avoidance, the effect is simultaneously significant.